LOCAL WISDOM-BASED ACCOUNTABILITY AS AN EFFORT TO PREVENT CORRUPTION OF ZAKAT FUNDS IN INDONESIA: A Case Study at BAZNAS Kebumen Regency, Central Java Province - Novendi Arkham Mubtadi; Dewi Susilowati (Asia Pacific Fraud Journal, 2018)
The purpose of this study is to measure and analyse the accountability of zakat institutions in Indonesia which is based on local wisdom values. This study is conducted with qualitative approach by using BAZNAS Kebumen Regency as the research sample. The result shows that for the past 4 years, there have been fluctuations in zakat disbursement program at BAZNAS Kebumen. In addition, this study also examines how the zakat institution has improved in terms of disbursement activities. The result of this research is expected to be useful for future discussions on the potential ways to prevent corruption of zakat funds in Indonesia. Thus, the outcomes of the discussions would be useful guide for policymakers in improving the zakat institution’s disbursement system.